ANALISIS FINANSIAL AGROINDUSTRI TAHU PASCA ISU TAHU BERMORFALIN DI KABUPATEN BANYUMAS - Wijayanti, Irene Kartika Eka; Mulyani, Altri (Universitas Sebelas Maret, 2009)
Tofu agroindustry in Banyumas Regency is the activity of the household who are still using relatively simple technology. In general, producer don’t know the factors that affect profits because they don’t consider in detail about the financial aspects of the business. The growing issue of making use of formalin in the tofu start early January 2006 has resulted in sales earnings of tofu producer the decline. Financial feasibility evaluation is required as a financial tool inspector companies, namely to know the success of the business that have beenrun. This study aimed to know the cost and income from agroindustry business in Banyumas Regency, to know the level of the revenue and cost (R/C), to calculates that production must be generated at least, to know the term capital in agroindustry in Banyumas Regency post issues formalin in tofu.Taking the data on January 2007 is done in the district of Cilongok, Banyumas Regency consideration is a regional industrial center of tofu in the Banyumas Regency. The research method is a method used by the design of the survey sample Simple Random Sampling and obtained 62 people respondents. The analysis of data used consist of the analysis of costs and revenue, R/C ratio analysis, break even point analysis, and Return on Invesment (ROI) analysis.The results of this research shows that the agroindustry business in the post-issue formalin in tofu in Banyumas Regency is profitable. The average income of each producer is Rp 78.626,33 per day. R/C value ratio of 1,46; while the actual volume of sales per day (63,70 kg) more than the production of the BEP (20,68 kg), with a term of capital at the latest 2,25 times the production process.